Protecting Well-Known Marks Related to Territorial Principle: From Substantive Similarity to the Distinctiveness Theory - Ni Ketut Supasti Dharmawan; Putu Samsithawrati; I Gede Agus Kurniawan; Rafika Amalia (Warmadewa Press, 2024)
Well-known marks are vulnerable to violations, including in Indonesia. Registered trademark disputes often occur between well-known and local mark owners regarding substantive similarities with well-known marks. Ironically, the dominant dispute resolution protects local marks with the rationality of mark protection based on Territorial Principles. The purpose of this study is to clarify how well-known marks are protected related to the exception applying the Territorial Principle to substantively similar marks and to examine the advantages of the Distinctiveness Theory for more legal certainty. The study used a normative legal research method. Study reveals that the Territorial Principle applies to mark protection through Article 6 of the Paris Convention, Article 15 of TRIPs, Article 3 of Indonesian Law No.20/2016 on Mark and Geographical Indication. Protection of Well-Known Marks is excluded from the Territorial Principle as agreed in 1925 by member countries of the Paris Convention. The exception arrangements are through Article 6bis of the Paris Convention, Article 16 of the TRIPs Agreement, and Article 21 of Law No.20/2016. Marks that are substantively similar with similar elements in visuals, phonetics, and concepts are important for mark examiners, law enforcers, and the public to understand. Understanding the mark distinctiveness theory from the weakest to the strongest, namely: Generic, Descriptive, Suggestive, Fanciful, and Arbitrary as an alternative solution for advantages in mark registration. That will also minimize mark disputes. Good faith in the mark registration is referring to uniqueness theory, it is able to differentiate items or services.